Clinical Practice Guideline for Solid Organ Donation and Transplantation During the COVID-19 Pandemic. Issue 10 (7th September 2021) - Weiss, Matthew J.; Hornby, Laura; Foroutan, Farid; Belga, Sara; Bernier, Simon; Bhat, Mamatha; Buchan, C. Arianne; Gagnon, Michael; Hardman, Gillian; Ibrahim, Maria; Luo, Cindy; Luong, Me-Linh; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The coronavirus 2019 (COVID-19) pandemic has disrupted health systems worldwide, including solid organ donation and transplantation programs. Guidance on how best to screen patients who are potential organ donors to minimize the risks of COVID-19 as well as how best to manage immunosuppression and reduce the risk of COVID-19 and manage infection in solid organ transplant recipients (SOTr) is needed. Methods: Iterative literature searches were conducted, the last being January 2021, by a team of 3 information specialists. Stakeholders representing key groups undertook the systematic reviews and generation of recommendations using a rapid response approach that respected the Appraisal of Guidelines for Research and Evaluation II and Grading of Recommendations, Assessment, Development and Evaluations frameworks. Results: The systematic reviews addressed multiple questions of interest. In this guidance document, we make 4 strong recommendations, 7 weak recommendations, 3 good practice statements, and 3 statements of "no recommendation." Conclusions: SOTr and patients on the waitlist are populations of interest in the COVID-19 pandemic. Currently, there is a paucity of high-quality evidence to guide decisions around deceased donation assessments and the management of SOTr and waitlist patients. Inclusion of these populations in clinical trials of therapeutic interventions, including vaccine candidates, is essential to guide best practices.